Brentuximab vedotin plus bendamustine in relapsed or refractory Hodgkin's lymphoma: an international, multicentre, single-arm, phase 1–2 trial. Issue 2 (February 2018) - O'Connor, Owen A; Lue, Jennifer K; Sawas, Ahmed; Amengual, Jennifer E; Deng, Changchun; Kalac, Matko; Falchi, Lorenzo; Marchi, Enrica; Turenne, Ithamar; Lichtenstein, Renee; Rojas, Celeste; Francescone, Mark; et al.
Summary: Background: Brentuximab vedotin is currently approved for patients with relapsed or refractory Hodgkin's lymphoma who previously received an autologous stem cell transplant or two previous multiagent chemotherapy regimens, and for patients with relapsed or refractory systemic anaplastic large-T-cell lymphoma who previously received at least one chemotherapy regimen. A high proportion of patients with CD30-expressing relapsed or refractory lymphomas have durable responses to single-agent brentuximab vedotin and show longer progression-free survival than do patients treated with chemotherapy. In patients with Hodgkin's lymphoma and peripheral T-cell lymphoma, treatment with bendamustine alone only achieves modest improvements in progression-free survival compared with that for chemotherapy. The objective of this study was to explore the safety and clinical activity of the combination of brentuximab vedotin plus bendamustine in heavily pretreated patients with relapsed or refractory Hodgkin's lymphoma and anaplastic large-T-cell lymphoma. Methods: In this international, multicentre, single-arm, phase 1–2 trial, eligible patients were aged 18 years or older, had histologically confirmed relapsed or refractory Hodgkin's lymphoma or anaplastic large-T-cell lymphoma, had biopsy-proven CD30-positive tumours, had an Eastern Cooperative Oncology Group performance status of 2 or less, and received at least one previous multiagent chemotherapy regimen. In phase 1, patients were assigned following a 3+3 dose-escalation design to one of four cohorts to receive one dose of either 1·2 mg/kg or 1·8 mg/kg of brentuximab vedotin intravenously on day 1 of a 21 day cycle, plus one dose of bendamustine (70 mg/m 2, 80 mg/m 2, or 90 mg/m 2 ) on days 1 and 2 of the treatment cycle. In phase 2, all patients were assigned to receive brentuximab vedotin plus bendamustine at the recommended phase 2 dose from phase 1. The primary endpoints were maximum tolerated dose and dose-limiting toxicity for phase 1, and the proportion of patients achieving an overall response in phase 2. For both phases 1 and 2, all patients receiving at least one dose of study drug were evaluable for toxicity and all patients completing at least one cycle of therapy were evaluable for response. The study is ongoing but no longer recruiting patients. This trial is registered withClinicalTrials.gov, numberNCT01657331 . Findings: Between July 26, 2012, and May 31, 2017, we enrolled and assigned 65 patients to treatment (64 [98%] with Hodgkin's lymphoma and one [2%] with anaplastic large-T-cell lymphoma; 28 [43%] during phase 1 and 37 [57%] during phase 2). In the phase 1 part, the maximum tolerated dose of the combination was not reached. Dose-limiting toxicities were observed in three (11%) of 28 patients, including grade 4 neutropenia at 1·8 mg/kg brentuximab vedotin plus 80 mg/m 2 of bendamustine in two (7%) patients and diffuse rash at 1·2 mg/kg brentuximab vedotin plus 70 mg/m 2 of bendamustine in one (4%) patient. The recommended phase 2 dose was deemed to be 1·8 mg/kg of brentuximab vedotin and 90 mg/m 2 of bendamustine, which are the standard doses of the drugs when given as single agents. In the phase 2 part, an overall response was achieved in 29 (78% [95% CI 62–91]) of 37 patients. Serious adverse events included grade 3 lung infection in five (14%) of 37 patients in the phase 2, and grade 3–4 neutropenia in 16 (25%) of 65 patients across phases 1 and 2. There were no treatment-related deaths. Interpretation: This study shows that brentuximab vedotin plus bendamustine, with a favourable safety profile, is an active salvage regimen for heavily pretreated patients with relapsed or refractory Hodgkin's lymphoma. This salvage regimen can potentially serve as an efficacious and safe alternative to platinum-based chemotherapy before autologous stem cell transplant. Funding: Seattle Genetics, Lymphoma Research Fund of Columbia University and National Center for Advancing Translational Sciences, and National Institutes of Health.